IMPLEMENTASI PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA DIKLAT PRODUKTIF KOMPETENSI MENGELOLA KARTU PIUTANG - Kusmuriyanto, -; Burhan, - (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
Beginning observation in vocational school Cut Nya’Dien show that result of study in accounting subject is low. The result of middle semester year 2006/2007 with completed study only 31% of 36 student. STAD Cooperative learning increase the result of study. Proved with the increation number of mean in each cycle are cycle I (59.23), cycle II (69.09), cycle III (81.23). Affective result of study, classical study completing reach 45.7% in cycle I, while in a cycle II reach 62.8%, and in cycle III reach 77.14%. So, in a cycle III the result of study in cognitive and affective of student increase. Cooperative learning model STAD could be as an alternative learning for the teacher in the way to increase the result of study. Be expected teacher facilitating book as a complementary in learning process to increase student knowledge, and motivate student to be active in learning process individually and group Key words : STAD cooperative learning, the result of study, managed account receivable.